The Construction of Fair Use of Copyright and Compensation System for Artificial Intelligence Creation - Shen Xiaoyun; Li Xiaofu (Global Legal Review, 2026)
The AI-generated works must intersect with the right holder’s work, thus having a certain impact on the rights and interests of the right holder’s work. The law needs to explore and improve the regulation of the fair use of AI creations and build a compensation system to adapt to the development of AI. The development of AI technology has brought about problems such as the unclear relationship between fair use and infringement of copyright, the unclear general terms and conditions of application, and the incomplete criteria for judging at different stages. Through different theoretical methods, the legitimacy of the rational use of the system can be demonstrated. The compensation standard for fair use of copyright in AI creation can refer to the market pricing of the right holder's work, and the compensation can construct a formula for the amount of damages for AI copyright infringement. The compensation standard should be based on the main factors affecting the market value of the work, so as to provide a reference for the compensation system of the fair use works generated by AI.